Linking hydro-morphology with invertebrate ecology in diverse morphological units of a large river-floodplain system - Blettler, Martin Cesar Maria (2016)
Interdisciplinary research in the fields of ecohydrology and ecogeomorphology is becoming increasingly important as a way to understand how biological and physical processes interact with each other in river systems. The objectives of the current study were 1) to determine changes in invertebrate community due to hydrological stages, 2) to link local physical features [flow configuration, sediment composition and morphological feature) with the ecological structure between and within dissimilar morphological units (meander and confluence), and 3) to determine the existence and the origin of bed hydro-geomorphic patches, determining their ecological structure. Results were discussed in the frame of prevailing ecological models and concepts. The study site extends over a floodplain area of the large Paran River (Argentina), including minor and major secondary channels as well as the main channel. Overall results suggested that hydrodynamics was the driving force determining distribution patterns of benthic assemblages in the floodplain. However, while the invertebrates living in minor secondary channels seem to benefit from flooding, this hydrological phase had the opposite effect on organisms from the main and major secondary channels. We also found a clear linkage between physical features and invertebrate ecology, which caused a dissimilar fauna structure between and within the meander and the confluence. Furthermore, several sandy-patches were recorded in the confluence. These patches were colonized by the particular benthic assemblage recorded in the main channel, supported the view of rivers as patchy discontinua, under uncertain ecological equilibrium.